THE FOUR FACTORS DOMINATING ONLINE STREAMING PLATFORMS AS WITNESSED BY NETFLIX IN THE WAKE OF GLOBALIZATION - Sekartaji, Swelana (Pengkajian Amerika, Universitas Gadjah Mada, 2023)
The globalization process has increased everything's accessibility and connectivity. Through information and technology, globalization makes it easier to move products, services, cultures, innovations, and creative ideas. As one of the most popular online streaming services, Netflix is fostering cross-cultural exchanges as part of the increasing globalization of capitalism. The author uses written sources, information, and evidence in the form of quotes from written works, written papers, and written responses to articles, reports, publications, and statistical data that are pertinent to Netflix. The author will apply globalization theory and a transnational approach to investigate why individuals favor Netflix over alternative online streaming services. These two theories are implemented in elaborating four dominant factors that Netflix has influenced the new habit patterns in today's society. Market growth will always play a role in globalization-related economic and cultural activities and processes. As a result, four key elements affect Netflix’s market dominance: substitution, barriers to entry and potential competition, measures of profitability, and market share.